"Fanaticism" and the Politics of Resistance along the North-West Frontier of British India. (14th July 2016) - Condos, Mark
Abstract: During the past decade, discussions of religious extremism and "fanatical" violence have come to dominate both public and academic discourse. Yet, rarely do these debates engage with the historical and discursive origins of the term "fanatic." As a result, many of these discussions tend to reproduce uncritically the same Orientalist tropes and stereotypes that have historically shaped the way "fanaticism" and "fanatical" violence have been framed and understood. This paper seeks to provide a corrective to this often problematic and flawed understanding of the history of "fanaticism." It approaches these topics through an examination of how British colonial authorities conceived of and responded to the problem of "murderous, " "fanatical, " and " ghazi " "outrages" along the North-West Frontier of India. By unpacking the various religious, cultural, and psychiatric explanations underpinning British understandings of these phenomena, I explore how these discourses interacted to create the powerful legal and discursive category of the "fanatic." I show how this was perceived as an existentially threatening class of criminal that existed entirely outside the bounds of politics, society, and sanity, and therefore needed to be destroyed completely. The subjectification of the "fanatic, " in this case, ultimately served as a way of activating the colonial state's "sovereign" need to punish and kill. Finally, I deconstruct these reductive colonial representations of fanaticism in order to demonstrate how, despite British views to the contrary, these were often complex and deeply political acts of anti-colonial resistance.